Controle supervisório da cadeia produtiva do biodiesel da mamona baseado em redes de Petri - Prata, Bruno de Athayde (2007)
Nowadays many countries present critical problems related to energy demand-supply equilibrium. The reserves of petroleum-based products are unable to face future demand for the next decades. So, the search for alternative sources of energy has been strongly directed to biodiesel. Several fruit oils can be used as a source for biodiesel production and the castor bean is an example. The castor bean agribusiness is a complex commodity chain, making necessary researches for the conception of this incipient chain. Discrete Event Systems (DES) are largely used in the modeling of commodity chains, aiding the planning and the manage of these systems. Among the DES modeling techniques, the Petri nets stands out for as making a easier a compact representation of a system and for permitting its simulation and analysis. The supervisory control aims for synthesize a supervisor that coordinate the activities of the subsystems in order to satisfy a set of specifications in a general system. The general purpose of this work was create a model, based on Petri nets, that permit the supervisory control of Castor Bean Biodiesel Supply Chain (CBB/SC) in order to guarantee its efficiency and efficacy. It was developed a new method for the supervisory control based on colored Petri nets, called Constraints of Control on Decomposed Colors (CCDC). Also, it was proposed a new framework for the supervisory control in logistics systems. Functional specifications were established for found the system which had its performance evaluated, based on the lead time, through simulation of several operational scenarios. As conclusion, it seems clear that the CCDC method is a consistent approach for DES control, the proposed model helps in a better comprehension about the system in analysis and the supervisory control is a theory that can aid the decision making process in similar chains as CBB/SC